Obesity and Blame: Elusive Goals for Personal Responsibility - Schmidt, Harald (The Hastings Center report, 2013)
One of six commentaries on “Obesity: Chasing an Elusive Epidemic,” by Daniel Callahan, from the January-February 2013 issue.